High‐Performance Electro‐Optic Modulator on Silicon Nitride Platform with Heterogeneous Integration of Lithium Niobate. Issue 4 (12th February 2023) - Ruan, Ziliang; Chen, Kaixuan; Wang, Zong; Fan, Xuancong; Gan, Ranfeng; Qi, Lu; Xie, Yiwei; Guo, Changjian; Yang, Zhonghua; Cui, Naidi; Liu, Liu
Abstract: Silicon nitride (SiN) emerges as an important platform for ultralow loss photonic integrations with complementary metal‐oxide‐semiconductor compatibility. However, active devices, such as modulators, are difficult to realize on pure SiN due to the lack of any electro‐optic (EO) properties of the material. Here, an SiN and lithium niobate (LN) heterogenous integration platform supporting high‐performance EO modulators on SiN waveguide circuits is introduced. An efficient evanescent coupling structure is realized for low‐loss light transitions between the SiN waveguide and the LN ridge waveguide with a measured mode transition loss of only 0.4 dB. Based on this heterogeneous platform, an EO Mach–Zender interference modulator on SiN is built with unprecedented loss, efficiency, and bandwidth performances. A half‐wave voltage of 4.3 V with a modulation bandwidth of 37 GHz and an overall insertion loss of 1 dB is measured for a 7‐mm long device. Data transmission up to 128 Gb s −1 with a bit‐error‐rate of <2.4 × 10 ‐4 is also demonstrated. Abstract : A silicon nitride (SiN) and lithium niobate heterogenous integration platform on SiN waveguide circuits is introduced. An efficient evanescent coupling structure is realized for low‐loss light transitions between waveguides of different materials with a measured mode transition loss of 0.4 dB. An electro‐optic Mach–Zender modulator on SiN is built with unprecedented loss, efficiency, and bandwidth performances.